The role of peer mediation in the relationship between learning motivation, self-efficacy, and learning styles of vocational high school students - Ikha Ansahela; Tusyanah Tusyanah (Universitas Sarjanawiyata Tamansiswa, 2026)
This study aims to analyze the mediating role of peer relationships in the relationship between learning motivation, self-efficacy, and learning styles among students of the Office Management and Business Services vocational program (SMK MPLB). The background of this research is based on the importance of psychological and social factors in determining students’ learning success, particularly in vocational education settings that require practical and adaptive skills. The research employed a quantitative approach with an explanatory research design. Data were collected through questionnaires distributed to SMK MPLB students and analyzed using path analysis to examine both direct and indirect relationships among variables. The results show that learning motivation has a positive influence on self-efficacy and students’ learning styles. Self-efficacy also significantly contributes to the development of effective learning styles. In addition, peer relationships play a mediating role that strengthens the relationship between learning motivation and self-efficacy in shaping students’ learning styles. This indicates that social interaction among students significantly contributes to building confidence and more adaptive learning patterns. Thus, peer environment in schools functions not only as a social interaction space but also as a medium for strengthening the learning process. This study implies that teachers should pay attention to peer group dynamics in learning strategies to optimally enhance students’ motivation, self-efficacy, and learning styles.